Origins of the UV/X-ray relation in Arakelian 120. Issue 3 (22nd February 2022) - Mahmoud, R D; Done, C; Porquet, D; Lobban, A
ABSTRACT: We explore the accretion geometry in Arakelian 120 using intensive UV and X-ray monitoring from Swift . The hard X-rays (1–10 keV) show large amplitude, fast (few-day) variability, so we expect reverberation from the disc to produce UV variability from the varying hard X-ray illumination. We model the spectral energy distribution (SED) including an outer standard disc (optical), an intermediate warm-Comptonization region (UV and soft X-ray), and a hot corona (hard X-rays). Unlike the lower Eddington fraction AGN (NGC 4151 and NGC 5548 at L / LEdd ∼ 0.02 and 0.03, respectively), the SED of Akn 120 ( L ∼ 0.05 LEdd ) is dominated by the UV, restricting the impact of reverberating hard X-rays by energetics alone. Illumination from a hard X-ray corona with height ∼10  Rg produces minimal UV variability. Increasing the coronal scale height to ∼100  Rg improves the match to the observed amplitude of UV variability as the disc subtends a larger solid angle, but results in too much fast variability to match the UV data. The soft X-rays (connected to the UV in the warm-Comptonization model) are more variable than the hard, but again contain too much fast variability to match the observed smoother variability seen in the UV. Results on lower Eddington fraction AGN have emphasized the contribution from reverberation from larger scales (the broad-line region), but reverberation induces lags on similar time-scales to the smoothing, producing a larger delay than is compatible with the data. We conclude that the majority of the UV variability is therefore intrinsic, connected to mass-accretion rate fluctuations in the warm-Comptonization region.